A Trojan Horse for Positivism? A Critique of Mixed Methods Research - Giddings, L; Grant, B (Lippincott Williams & Wilkins, 2007)
Mixed methods research is captured by a pragmatically inflected form of postpositivism. Although it passes for an alternative methodological movement that purports to breach the divide between qualitative and quantitative research, most mixed methods studies favor the forms of analysis and truth finding associated with positivism. We anticipate a move away from exploring more philosophical questions or undertaking modes of enquiry that challenge the status quo. At the same time, we recognize that mixed methods research offers particular strengths and that, although it serves as a Trojan Horse for positivism, it may productively carry other paradigmatic passengers.
Keywords: Mixed methods; Qualitative research; Quantitative research; Paradigms; Post activism; Pragmatism